1998
DOI: 10.3109/07853899809029936
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between contrast sensitivity and metabolic control in diabetics with and without retinopathy

Abstract: Contrast sensitivity was studied in diabetic adolescents and young adults with and without retinopathy in order to evaluate their central vision, to analyze the relationship of metabolic control to the presence and severity of retinopathy, and to re-evaluate the response to this test after a significant improvement in metabolic control. Twenty adolescent and young adult diabetics without retinopathy and 40 diabetics with retinopathy of varying degree were enrolled in the study; 20 healthy age and sex-matched s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 28 publications
5
29
0
1
Order By: Relevance
“…Different factors were tested in correlation with the CS function. The same CSV-1000 testing instrument showed a positive relationship between metabolic control and CS in young IDDM patients with and without retinopathy [7]. In type 2 diabetic patients, contrast sensitivity deficits, determined by stationary grating, were positively correlated with the patient's age, blood pressure, and nephropathy [8], and in young IDDM (type 1), the patient's microalbuminuria was also found to be associated with reduced CS [9].…”
Section: Proprietary Interest Nonementioning
confidence: 94%
See 1 more Smart Citation
“…Different factors were tested in correlation with the CS function. The same CSV-1000 testing instrument showed a positive relationship between metabolic control and CS in young IDDM patients with and without retinopathy [7]. In type 2 diabetic patients, contrast sensitivity deficits, determined by stationary grating, were positively correlated with the patient's age, blood pressure, and nephropathy [8], and in young IDDM (type 1), the patient's microalbuminuria was also found to be associated with reduced CS [9].…”
Section: Proprietary Interest Nonementioning
confidence: 94%
“…Various techniques have been adopted to measure CS, and most of them reported a significant difference between diabetic and normal eyes. CS was tested in insulin-dependent diabetic patients (IDDM) and in noninsulin-dependent diabetic patients (NIDDM), both young and old [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Proprietary Interest Nonementioning
confidence: 99%
“…A sensitivity loss of phototransduction for both rods and cones, causing reduction in dark adaptation and loss of colour determination and contrast sensitivity, and an altered waveform response for both amacrine and bipolar cells, reflecting a diffused alteration in neuronal synaptic transmission, have been described [5,12,13,14,15,16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies in animal models of diabetes and in human subjects had shown an impairment of the innermost retinal layers [5,11,12] and of amacrine cells [12,13,14] as well as an impairment of the short-, mid- and long-wavelength cone components in different stages of the pathology [15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Contrast sensitivity is impaired (Di Leo, et al, 1992;Hyvarinen, et al, 1983;Liska and Dostalek, 1999;Sokol, et al, 1985;Stavrou and Wood, 2003;Verrotti, et al, 1998), as is contrast sensitivity for motion detection (Kawasaki, et al, 1986). Recovery from glare (retinal photo stress) is delayed and dark-adapted thresholds are elevated (Greenstein, et al, 1993;Parisi, et al, 1994;Spafford and Lovasik, 1986).…”
Section: Changes In Visionmentioning
confidence: 99%